Understanding teacher education within the scope of the model of semantic fields - De Paulo, João Pedro Antunes; Bicudo, Maria Aparecida Viggiani [UNESP] (My University, 2020)
Background: In Mathematics Education many works use the Model of the Semantic Fields (MSF) to investigate aspects of the teaching and learning Mathematics and teacher education. However, none of these works analyzes the development of this theoretical model or investigates the theories that support it. Objectives: present a meta-analysis of the results of the doctoral thesis (Paulo, 2020) which aimed to investigate the existence of a Mathematics teacher education project consistent with the MSF. Design: The study is part of a hermeneutics analysis based on the MSF's ways of proceeding. Setting and Participants: The research has a bibliographic nature and was developed from 31 works published between the years 1992 and 2012. The selection of works that constituted the research corpus took place by consulting all works published by the research group Sigma-t, being elected those dealing with teacher education. Data collection and analysis: From the corpus of the research, an analysis was carried out according to the MSF's characteristic way of proceeding, explained in the item “Methodology” of this text. This analysis resulted in the production of a report from which the authors articulated their conclusions. Results: The study shows the existence of a teacher training project being articulated over the years by the researchers who make up the research group investigated. In a complementary way, a systematization of “Plausible Reading” also resulted from our analyzes as a research procedure based on the MSF. Conclusions: We conclude this article by pointing out the potential and limitations of the research developed during the PhD, as well as referrals for the research developed.
Keywords: Mathematics Education; Model of Semantic Fields; Plausible reading; Qualitative research; Teacher education